Preparation and Application of Natural and Low Cost Palm Fibers as an Effective Drag Reducing Agent for Flow Improvement in Iraqi Crude Oil Pipelines - Ibrahim, Raheek I.; Odah, Manal K.; Shafeeq, Dhoha A. (Anbar Journal of Engineering Science, 2020)
Flow of crude oil in pipelines suffers from a problem of fluid flow pressure drop and high energy consumption for fluid pumping. Flow can be enhanced using either viscosity reduction or drag reduction techniques. Drag reduction (DR) is considered as a most effective and most applicable method. The technique contributes in reducing the frictional energy losses during the flow by addition of little amounts from drag reducing agents. The present work focuses on preparation and application of a new natural and low cost material derived from palm fiber (PF) that has been tested as a drag reducing agent (DRA) for crude oil flow enhancement. This objective has been achieved through designing and constructing of an experimental rig consisting of: a crude oil pipe, oil pump, pressure sensors, solenoid valve and programmable logic control. The additive material (PF) is prepared with different diameters (75µm, 125µm, 140µm) and tested with different concentrations as: 100, 200, 300, 400, and 500 mg/L for reducing the drag inside the oil pipe. The experimental results showed that the fiber with 125µm diameter and 100ppm is the best where the percentage of drag reduction reached 43%. Furthermore, the results of this work proved that PF is an efficient and low cost DRA that can be applied successfully in crude oil pipelines as well as its contribution in the waste management.